Оценка статической трещиностойкости полимерных материалов для изготовления базисов съемных протезов - Макєєв, Валентин Федорович; Скальський, Валентин Романович; Гуньовський, Ярослав Романович; Гуньовська, Романа Петрівна (Actual Dentistry, 2019)
Resume. The intensity of scientific research in the field of new basic polymer materials shows both the importance and the complexity of creating a high-strength, convenient, cheap material for dentistry without significant technological changes. However, a number of studies on biodestruction of basic plastics, studying the mechanical strength of their samples do not affect the problems and causes of origin, the spread of cracks in the thickness of the prosthesis, resulting in its destruction. Therefore, the development of a technique for determining the origin of cracks in basic materials is important in lengthening the operational properties of removable prostheses. The goal. Comparative evaluation of material static crack resistance for removable dentures bases and the destruction of polymers by the tensile method according to the scheme of three-point bending by a quasi-static load. We investigated the destruction of samples during quasi-static tensile of three types of materials: «Ftoraks» (JSC «CTOMA», Ukraine), «Villacryl H Plus» (Zhermack, Italy), «Vertex™ ThermoSens» (Vertex Dental, Netherlands) using acoustic emission method. Results. According to research results, all polymers were destroyed in a linearly elastic way. The largest AE activity was observed during the stretching of the «Ftoraks» polymer samples, and the smallest – «Villacryl H Plus». Achievement of the load of destruction in different materials requires different times: the largest amount of time for «Vertex™ TermoSens» polymer, the least – for «Ftoraks». Conclusions. Comparative evaluation of samples showed that, according to experimental data, materials for bases of removable dentures on the ability to resist cracking (first appearance of AE signals) can be divided in this order (from the most durable to the weakest): «Villacryl H Plus», «Vertex™ TermoSens», «Ftoraks», and bymacro-indicator of viscosity fracture КІС – «Vertex™ TermoSens», «Ftoraks», «Villacryl H Plus». Key words: polymeric materials, removable dentures, acoustic emission, three-point bending, quasi-static tensile.